Образ сучасного героя російсько-української війни: кваліфікаційна робота на здобуття освітнього ступеня «Бакалавр»; спец.: «061 – Журналістика»; наук. керівник Н. С. Подоляка - Іванченко, Юлія Володимирівна (Ніжин. НДУ ім. Миколи Гоголя, 2024. 64 с., 2024)
У роботі висвітлено сутність понять «медіаобраз» «образ героя війни», «післяправда», «гібридна війна», «героїчні архетипи», проаналізовано історичний контекст формування образу героя. Описано тенденції впливу постправди і гібридної війни. За методом контент-аналізу досліджено словотипи образу героя російсько-української війни, визначено 1118 слововживань, здійснено типологізацію образів. Проведено соціологічне опитування для визначення впливу образу героя на суспільну думку.
The image of a modern hero of the Russian-Ukrainian war: qualification work for obtaining the educational degree «Bachelor»; special: «061 – Journalism»; of science manager N. S. Podolyakа
The work highlights the essence of the concepts «media image», «image of a war hero», «post-truth», «hybrid war», «heroic archetypes», and analyzes the historical context of the formation of the image of a hero. The trends of influence of post-truth and hybrid war are described. According to the method of content analysis, the word types of the image of the hero of the Russian-Ukrainian war were studied, 1118 word usages were identified, and typology of the images was carried out. A sociological survey was conducted to determine the influence of the image of the hero on public opinion.
Keywords: медіаобраз, образ героя війни, селебритіз, імідж, постправда (післяправда), концепт, гібридна війна.; media image, image of a war hero, celebrities, image, post-truth (post-truth), concept, hybrid war.